Fungsi World Food Programme (WFP) Dalam Penanganan Krisis Pangan Di Negara Berkonflik - Nur Afifa S Rumbia; Efie Baadila; Veriana Josepha Batseba Rehatta (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: The World Food Program or abbreviated as WFP is a special organization of the United Nations in collaboration with the Food Agriculture Organization which aims to deal with food crises, hunger, emergencies quickly in the provision of food in developing countries experiencing food crises. Purposes of the Research: Aims to know the function of WFP in the organizational structure of the United Nations, and to know WFP's responsibilities in handling food crises in conflict countries.Methods of the Research: The research method used in writing this thesis is normative legal research or library research, namely, legal research conducted by examining primary and secondary legal materials.Results of the Research: The results show that in carrying out humanitarian programs by WFP, it does not always run smoothly, there are also obstacles and challenges that must be faced by WFP in carrying out their duties and functions in the form of political instability in a country, limited access to areas, where it is difficult to access roads to the locations to be visited. assistance, and very limited funding. WFP's main programs in overcoming the food crisis in Afghanistan are School Meals, Take Home rations, Food for Training, and Food for Work.